ANALYSIS OF TOURISM ACTIVITIES AT THE JAKARTA PUPPET MUSEUM - Hasna Nabilah Kurnia; Irena Novarlia; Dally Nur Arif (SOSIOEDUKASI, 2026)
This study aims to analyze tourism activities at the Wayang Museum Jakarta as a cultural tourism destination, viewed from the aspects of experience, entertainment, and satisfaction. The research employs a qualitative approach with a case study method. Data were collected through direct observation, semi-structured interviews with museum management, guides, and visitors, as well as documentation. Data analysis followed the interactive model by Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings indicate that tourism activities at the Wayang Museum Jakarta are capable of creating meaningful educational experiences through guided tours, cultural workshops, and direct interaction with wayang collections. The entertainment aspect is realized through regular wayang performances and an immersive room that serves as the museum's primary attraction. Meanwhile, visitor satisfaction was rated favorably.